A atuação do(a) psicólogo(a) diante da morte no hospital: uma práxis na pandemia - Silva, Amanda Cecília Correia (Universidade Federal do Tocantins, 2023)
Death is something that confronts us with our human vulnerability, with our feelings about losses and our resources to deal with them. Considering death as something belonging to our reality, and the way it is inserted in hospitals, it is necessary to think about the possible forms of reception in these situations. The COVID-19 pandemic required an adaptation to care routines, bringing a new scenario with many restrictions. In this sense, the present work had as general objective to understand the meanings attributed by (a) hospital psychologist (a) regarding his performance in the face of death in the context of the covid-19 pandemic. The research had a qualitative and exploratory character, being used as a method the field research and a script of semi-structured interview as an instrument. The data were treated by Bardin content analysis. The results came from five categories of analysis related to the meanings related to action and practices in the face of death and dying developed during the pandemic period, highlighting their crossing in the lives of (the) professionals. It was concluded that the performance of the (a) psychologist (a) did not change in its structure, but that some clinical devices were added to it that can help in the elaboration of mourning in situations of social isolation. In addition, it is observed that the meanings of their performance in the pandemic, especially when it comes to death, are to have to deal with the unexpected and unpredictability, with the wisdom to work as a team and, finally, sustain the reception in terminality and death.